Balancing act between research and application: how research orientation and networks affect scholars' academic and commercial output - Claudia Werker; Christian Hopp (Journal of Business Economics, 2020)
Scholars' balancing act between research and application leads to trade-offs between commercial and research output. Yet what some scholars may consider as poles apart might lead to super-additive outcomes for others. Based on a survey carried out at three leading European universities of technology we investigate the influence of scholars' research orientation and networks on their output productivity. Our results point to a very specific group of ambidextrous scholars that is comparatively small. The scholars in this group are able to successfully balance research and application. In contrast, all scholars focusing on either pure basic or pure applied research face a trade-off between publications and innovations. In general, our findings suggest that the output productivity of all scholars is the higher the better their research orientation fits with their network activities. In particular, ambidextrous scholars rely on effectively accessing and utilizing their network to increase commercial and research output.
Keywords: O31; O38; J4; 650; Academia; Output; Research orientation; Networks; Ambidexterity